PERSPECTIVES OF THE DEVELOPMENT OF AGRICULTURE OF THE RUSSIA IN MODERN TIMES. RESULT OF WORK OF THE COMMITTEE OF THE STATE DUMA ON NATURAL RESOURCES, MANAGEMENT AND ECOLOGY - V. I. Kashin (Овощи России, 2016)
The perspectives of the development of agriculture in Russia in modern times and main results of work of the Committee of the State Duma on Natural Resources, Management and Ecology are presented in the article. For the purpose of food sovereignty, the import ration should not be exceeded 25% from overall volume of food production. The Russian Academy of Agricultural Science worked on the potential of agricultural sector, which has to be the duty-bearer of food supply security of Russia and the source of raw materials for the trade. Up to now, the Russian scientists have developed a lot of competitive varieties and hybrids, widespread commercial introduction of which is able to guarantee of high quality products.